Виклики та проблеми дошкільної освіти: український контекст - Рудницька-Юрійчук, Ірина Романівна (Українська Державна льотна академія, 2025)
The article provides a comprehensive analysis of the current challenges and problems facing the preschool education system in Ukraine in the context of social transformations, wartime realities, and integration into the European educational space. Preschool education is viewed as a fundamental stage of lifelong learning, shaping the child’s personality development, readiness for further schooling, and successful socialization. The study highlights key issues such as the shortage and aging of teaching staff, insufficient material incentives for educators, lack of qualified specialists for inclusive education, and limited material and technical resources of preschool institutions. Special attention is given to the development of inclusive education, which remains one of the most dynamic directions in Ukrainian preschool education. The problem of insufficient parental involvement in the educational process is also analyzed, as it reduces the effectiveness of pedagogical influence and negatively affects children’s emotional stability and adaptation in preschool groups. The article emphasizes the importance of implementing innovative teaching methodologies, interactive learning forms, digital technologies, and multimedia resources that enhance the quality of the educational process and foster creativity, communication skills, and critical thinking in children. The necessity of creating psychologically safe and emotionally supportive environments is also discussed, ensuring children’s well-being and motivation for learning. It is concluded that the effective development of preschool education in Ukraine requires a comprehensive approach, including reforms in teachers’ remuneration, modernization of material and technical infrastructure, professional training in inclusive education, strengthening family-school cooperation, and integration of modern educational technologies. Addressing these challenges will contribute to improving the quality, accessibility, and inclusiveness of preschool education while aligning it with the current needs of Ukrainian society and international standards
Keywords: виклики; дошкільна освіта; інклюзивність; інноваційні методики; кадрове забезпечення; матеріально-технічна база; проблеми; Україна